EVALUASI MORFOTEKTONIK SEBAGAI FAKTOR PENGONTROL LONGSORAN DI KAWASAN SESAR LEMBANG - Wildan, Dadan; Saputra, Adang; Sulastri, Murni; Sulaksana, Nana; Rendra, Pradnya Paramarta Raditya (Bulletin of Scientific Contribution, 2026)
ABSTRACTThe Lembang Fault is recognized as one of the major active fault structures in West Java with significant potential to trigger geological hazards, particularly earthquakes and landslides. The morphology of the area is characterized by steep slopes underlain by volcanic rocks that have undergone intensive weathering, making them highly susceptible to landslide. This study aims to examine the relationship between morphotectonic parameters, geological conditions, and landslide distribution in the northern part of the Bandung Basin. The analysis employs a quantitative geomorphological approach utilizing Digital Elevation Models (DEM) imagery and the calculation of morphotectonic indices, including Assymetric factor (Af), Basin shape index (Bs), Sinuosity of mountain front index (Smf), and valley floor width-to-height ratio (Vf). The findings indicate that most landslide occurrences are concentrated in areas with high Index of Relative Tectonic Activity (IRTA), reflecting both active tectonic deformation and unstable slope conditions. The integration of morphotectonic parameters with landslide data has proven effective in delineating hazard-prone zones with higher accuracy, thereby providing a valuable reference for geological hazard mitigation efforts in the Lembang Fault area.Keywords: Morphotectonic; geomorphology; landslide; Lembang Fault; Bandung Basin ABSTRAKSesar Lembang dikenal sebagai salah satu struktur patahan aktif di Jawa Barat yang memiliki potensi besar memicu bencana geologi, terutama gempabumi dan gerakan tanah. Morfologi wilayah ini didominasi oleh lereng curam dengan batuan vulkanik yang telah mengalami pelapukan intensif, sehingga rentan terhadap terjadinya longsoran. Penelitian ini bertujuan untuk menelaah keterkaitan antara parameter morfotektonik, kondisi geologi, dan distribusi longsor di bagian utara Cekungan Bandung. Analisis dilakukan melalui pendekatan geomorfologi kuantitatif dengan memanfaatkan citra Digital Elevation Model (DEM) serta penghitungan sejumlah indeks morfotektonik seperti Faktor asimetri DAS (Af), Indeks bentuk DAS (Bs), Indeks sinusitas muka gunung (Smf), dan Rasio dasar lembah berbanding tinggi lembah (Vf). Temuan penelitian mengindikasikan bahwa mayoritas kejadian longsor terkonsentrasi pada area dengan nilai Indeks Aktivitas Tektonik Relatif (IATR) tinggi, yang mencerminkan aktivitas tektonik aktif sekaligus lereng tidak stabil. Integrasi antara parameter morfotektonik dengan data longsoran terbukti efektif dalam memetakan zona rawan dengan tingkat akurasi lebih tinggi, sehingga dapat dijadikan acuan penting bagi upaya mitigasi bencana geologi di kawasan Sesar Lembang.Kata Kunci : Morfotektonik; geomorfologi; longsor; Sesar Lembang; Cekungan Bandung